Rates and localization of phosphorus fertilizer on onion yield - Weingartner, Sibeli; Gatiboni, Luciano Colpo; Dall’Orsoletta, Daniel João; Kurtz, Claudinei; Mussi, Muriá (Revista de Ciências Agroveterinárias, 2018)
The onion has a high response to phosphate fertilizers application. Even extrapolating official recommendations, the phosphorus (P) addition usually increase onion productivity. Due to the restricted root system, it is possible that phosphate fertilizer location in furrow enables more efficient use of nutrients, reducing P rates required for culture. The aim of this study was to evaluate the onion response to P rates, applied in furrow or broadcasted on soil surface, in a Humic Cambissol. Five rates of phosphate were tested (0, 120, 240, 360 and 480 kg P2O5 ha-1) and two application methods (broadcasted and in furrow) in a complete randomized design in factorial 5x2 with four replications. It was used onions EPAGRI 352 Bola Precoce, planted on 22/07/2014 and harvested on 15/11/2014. There was a linear response of onion to P fertilization and an increase in productivity of 16.7 kg of onions per each kilogram of applied P2O5; also it was increased by 0.08 mm bulb diameter per each kilogram of P2O5 applied. There was no response by onion to the method of P application (broadcasted or furrow), indicating that location of the fertilizer does not increase the efficiency of phosphorus fertilization in this culture.